2021
DOI: 10.1155/2021/4026604
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis to Identify Key Genes Involved in Advanced Atherosclerosis

Abstract: Background. The study was aimed at finding accurate and effective therapeutic targets and deepening our understanding of the mechanisms of advanced atherosclerosis (AA). Methods. We downloaded the gene expression datasets GSE28829, GSE120521, and GSE43292 from Gene Expression Omnibus. Weighted gene coexpression network analysis (WGCNA) was performed for GSE28829, and functional enrichment analysis and protein–protein interaction network analysis were conducted on the key module. Significant genes in the key mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Transcriptome analysis enables an expanded knowledge of complex multicellular biological systems, which has become a cornerstone of many research initiatives ( 23 , 24 ). In this study, we performed a series of bioinformatics analyses to identify the cluster gene module and immune cells infiltration patterns along with the underlying mechanistic pathways in the progression of atherosclerotic plaques.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome analysis enables an expanded knowledge of complex multicellular biological systems, which has become a cornerstone of many research initiatives ( 23 , 24 ). In this study, we performed a series of bioinformatics analyses to identify the cluster gene module and immune cells infiltration patterns along with the underlying mechanistic pathways in the progression of atherosclerotic plaques.…”
Section: Discussionmentioning
confidence: 99%
“…As a transmembrane receptor in neutrophils and monocytes/macrophages (54), TYROBP is involved in macrophage activation, lipid deposition and plaque inflammation. In the bioinformatics analysis reported by Liu et (58), TYROBP was found to be one of the key Genes Involved in Advanced Atherosclerosis. CSF1R plays an important role in the survival, proliferation and differentiation of macrophages and monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally considered important regulators of cell survival, proliferation, adhesion, and migration [41], De cient ITGB2 could also exert a neuroprotective effect by reducing in ltrating leukocytes, which decrease in ammatory cytokines and chemokines [42]. Bioinformatics analysis showed that ITGB2 expression was up-regulated in AS patients [43][44][45]. It may be an important biomarker of bleeding in atherosclerotic plaque [46].…”
Section: Discussionmentioning
confidence: 99%
“…A variety of in ammatory pathways are driven by TYROBP [49], As a result of its involvement in the TREM-1/DAP12 pathway, TYROBP accelerates atherosclerosis progression [50]. Bioinformatics analysis showed that the expression of TYROBP was also signi cantly up-regulated in AS patients [44], It may be an important biomarker of atherosclerotic plaque bleeding [51]. Researchers found that TYROBP is a hub gene for immune response in advanced atherosclerosis, according to Chiyu Liu et al, In the treatment of advanced atherosclerotic plaque, it may be a potential interventional target [52].…”
Section: Discussionmentioning
confidence: 99%